Racial and Ethnic Disparities in Graft and Recipient Survival in Elderly Kidney Transplant Recipients. Issue 12 (11th December 2015) - Ilori, Titilayo O.; Adedinsewo, Demilade A.; Odewole, Oluwaseun; Enofe, Nosayaba; Ojo, Akinlolu O.; McClellan, William; Patzer, Rachel E.
Abstract : Objectives: To investigate racial and ethnic differences in graft and recipient survival in elderly kidney transplant recipients. Design: Retrospective cohort. Setting: First‐time, kidney‐only transplant recipients aged 60 and older of age at transplantation transplanted between July 1996 and October 2010 (N = 44, 013). Participants: United Network for Organ Sharing (UNOS) database. Measurements: Time to graft failure and death obtained from the UNOS database and linkage to the Social Security Death Index. Neighborhood poverty from 2000 U.S. Census geographic data. Results: Of the 44, 013 recipients in the sample, 20% were black, 63% non‐Hispanic white, 11% Hispanic, 5% Asian, and the rest "other racial groups." In adjusted Cox models, blacks were more likely than whites to experience graft failure (hazard ratio (HR) = 1.23, 95% confidence interval (CI) = 1.15–1.32), whereas Hispanics (HR = 0.77, 95% CI = 0.70–0.85) and Asians (HR = 0.70, 95% CI = 0.61–0.81) were less likely to experience graft failure. Blacks (HR = 0.84, 95% CI = 0.80–0.88), Hispanics (HR = 0.68, 95% CI = 0.64–0.72), and Asians (HR = 0.62, 95% CI = 0.57–0.68) were less likely than whites to die after renal transplantation. Conclusion: Elderly blacks are at greater risk of graft failure than white transplant recipients but survive longer after transplantation. Asians have the highest recipient and graft survival, followed by Hispanics. Further studies are needed to assess additional factors affecting graft and recipient survival in elderly adults and to investigate outcomes such as quality of life.